Genetic Characterization of a Novel Bovine Rotavirus A G37P[52] Closely Related to Human Strains - Singh, Vikash K.; Neira, Victor; Brito, Barbara; Ariyama, Naomi; Sturos, Matt; Mor, Sunil K. (Frontiers in Veterinary Science, 2022)
Bovine rotavirus A (boRVA) strains are common causative agents of diarrhea in calves, resulting in economic losses to the beef and dairy industry. Importantly, this virus has a zoonotic relevance due to its ability to reassort with human rotaviruses. In this study, fecal samples were collected from three calves with diarrhea during an outbreak on a dairy farm. The genetic material of boRVA was detected by real-time reverse transcription PCR (rtPCR) in two samples. Then the virus in one of these positive samples was identified as a novel boRVA genotype closely related with human rotavirus strains mainly from the USA based on whole-genome characterization. However, we consider the novel boRVA as the etiological agent of the outbreak due to the lesions associated with a rotavirus infection. Further studies are necessary to clarify the evolutionary advantages that novel rotavirus genotypes may have.